2021
DOI: 10.1080/22221751.2021.1984182
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in porin LamB contribute to ceftazidime-avibactam resistance in KPC-producing Klebsiella pneumoniae

Abstract: Ceftazidime-avibactam (CAZ-AVI) shows promising activity against carbapenem-resistant Klebsiella pneumoniae (CRKP), however, CAZ-AVI resistance have emerged recently. Mutations in KPCs, porins OmpK35 and/or OmpK36, and PBPs are known to contribute to the resistance to CAZ-AVI in CRKP. To identify novel CAZ-AVI resistance mechanism, we generated 10 CAZ-AVI-resistant strains from 14 CAZ-AVI susceptible KPC-producing K. pneumoniae (KPC-Kp) strains through in vitro multipassage resistance selection using low conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…One study reported the impact of colistin in decreasing the expression of the maltose transporter LamB, a porin involved in the influx of antibiotics and the class A β lactamases—TEM, SHV-11, and SHV-4 [ 165 ]. Comparative proteomic analysis of polymyxin-susceptible Klebsiella pneumoniae validated the role of crrB -mediated colistin resistance in which lipid A profiles presented the addition of one or two L-Ara4N molecules and palmitoylation with elevations in CrrAB, PmrAB, and ArnBCADT levels.…”
Section: Proteomic Studies On Eskape Resistancementioning
confidence: 99%
“…One study reported the impact of colistin in decreasing the expression of the maltose transporter LamB, a porin involved in the influx of antibiotics and the class A β lactamases—TEM, SHV-11, and SHV-4 [ 165 ]. Comparative proteomic analysis of polymyxin-susceptible Klebsiella pneumoniae validated the role of crrB -mediated colistin resistance in which lipid A profiles presented the addition of one or two L-Ara4N molecules and palmitoylation with elevations in CrrAB, PmrAB, and ArnBCADT levels.…”
Section: Proteomic Studies On Eskape Resistancementioning
confidence: 99%
“…Resistance of A. baumannii strains to CAZ/AVI is due mainly to the failure of AVI to penetrate the outer membrane (Mushtaq et al, 2010). In addition to OmpC, OmpF, and their homologous proteins, the introduction of a wild-type Lamb into resistant strains carrying a variant Lamb with Arg33His and Arg374Leu substitutions results in a 2-fold reduction in the MIC values of these strains for CAZ/AVI, indicating that variant Lamb contributes to resistance to CAZ/AVI (Guo et al, 2021).…”
Section: Caz/avi Resistance Associated With Changes In Bacterial Memb...mentioning
confidence: 99%
“…Culture of strains susceptible to CAZ/AVI in LB medium containing CAZ/AVI for 50 generations resulted in the generation of several variants of KPC‐2, such as a 165_166 Gln‐Leu insertion, a Leu169Pro insertion plus a Ser181 insertion, and a 166_167 Gln‐Leu deletion. Introduction of these bla KPC mutations into a wild‐type strain susceptible to CAZ/AVI increased the MIC values for CAZ/AVI from 2/4, 4/4, and 0.25/4 mg/L to 16/4, 128/4, and 32/4 mg/L, respectively, but did not affect MIC values for CAZ significantly, suggesting that these variants mainly affect the inhibitory activity of AVI (Guo et al, 2021 ).…”
Section: Mechanisms Underlying Resistance To Caz /...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies ( 3 5 ) on the treatment of CRE infections have been particularly focused mostly on new antibiotics, including β-lactam–β-lactamase inhibitor combinations (e.g., ceftazidime-avibactam, ceftolozane-tazobactam, and meropenem-vaborbactam), and other existing antibiotics (e.g., aminoglycosides, carbapenems, and tigecycline, etc.). However, these new antibiotics have been on the market in recent years yet drug resistance still appears worldwide ( 6 8 ). Therefore, the spread of CRE is a clinical and public health problem.…”
Section: Introductionmentioning
confidence: 99%